Thermodynamic mechanism of the density anomaly of liquid water - Yasutomi, Makoto (Frontiers in Physics, 2015)
Although density anomaly of liquid water has long been studied by many different authors up to now, it is not still cleared what thermodynamic mechanism induces the anomaly. The thermodynamic properties of substances are determined by interparticle interactions. We analyze what characteristics of pair potential cause the density anomaly on the basis of statistical mechanics and thermodynamics using a thermodynamically self-consistent Ornstein-Zernike approximation (SCOZA). We consider a fluid of spherical particles with a pair potential given by a hard-core repulsion plus a soft-repulsion and an attraction. We show that the density anomaly occurs when the value of the soft-repulsive potential at hard-core contact is in some proper range, and the range depends on the attraction. Further, we show that the behavior of the excess internal energy plays an essential role in the density anomaly and the behavior is mainly determined by the values of the soft-repulsive potential, especially near the hard core contact. Our results show that most of ideas put forward up to now are not the direct causes of the density anomaly of liquid water.